Analisis Pola Penyebaran dan Dampak Virus Trojan Horse terhadap Keamanan Sistem Komputer - Gilang Akbar Hadikosyah; Nurul Firzatul Zannah; Sara Yulistia; M Rizky Febrian; Fhadli Maulana; Rianda Sulthan (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of information technology has significantly increased the use of computer systems in daily activities. Alongside these developments, cyber threats have also grown, one of the most prevalent being the Trojan Horse virus. Trojan Horse is a type of malware that disguises itself as a legitimate program in order to deceive users and gain unauthorized access to computer systems. This study aims to analyze the patterns of Trojan Horse virus propagation, examine its impacts on computer system security, and identify effective prevention and mitigation strategies. The research method used is a literature review by analyzing books, scientific journals, and credible online sources related to Trojan Horse malware and information system security. The results show that Trojan Horse viruses commonly spread through email attachments, malicious downloads, fake software, and social engineering techniques. The impacts include data theft, system performance degradation, unauthorized remote access, and disruption of organizational operations. Therefore, comprehensive security measures combining technical controls and user awareness are essential to minimize Trojan Horse attacks.